Understanding the role of investment decisions, free cash flow, and asset intensity in financial distress - Azzahra, Dela Novera; Praptiningsih, Praptiningsih (Journal of Management and Digital Business, 2026)
This study examines the effect of investment decisions, free cash flow, and asset intensity on financial distress in manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Using panel data from 141 firms with 564 observations, financial distress is measured by the Altman Z’-Score and analyzed through multiple linear regression employing the Random Effect Model. The results indicate that asset intensity has a significant negative effect on financial distress, while free cash flow has a significant positive effect, whereas investment decisions show no significant effect. These findings highlight the importance of asset utilization efficiency and effective oversight of free cash flow in reducing the risk of financial distress, and they support Agency Theory regarding the role of managerial monitoring in the management of corporate assets and cash. The study contributes to the literature by providing empirical evidence from a post-pandemic context, where firms face structural adjustments in financial and operational strategies.